The influence of readibility of examination questions on achievement in senior secondary school mathematics : a study on verbal problems with special reference to second language readers - Prins, Elizabeth Diana (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1995.